Effects of hysteresis, rainfall dynamics, and temporal resolution of rainfall input data in solute transport modelling in uncropped soil. Issue 5 (3rd April 2016) - Persson, Magnus; Saifadeen, Alan
ABSTRACT: Numerical simulations were carried out using the HYDRUS 1D model for three different types of uncropped soils. Input data were observed of rainfall during a 15-year period at three sites in Sweden. Simulations were run with and without consideration of hysteresis. Three different rainfall input time steps were used: 0.5, 4, and 24 h. Solute transport was evaluated using the centre of mass (zCOM ) of breakthrough curves (BTCs) and largest depth where a pre-defined limit concentration was exceeded (zLC ). Results showed that hysteretic flow was slower as compared to the non-hysteretic case. Results also showed that zCOM generally had a positive correlation with the number of high-intensity rainfalls and that the correlations were higher for the non-hysteretic case. The results show that it is important to use a sufficiently short rainfall input time step and an accurate description of the soil hysteresis when assessing the effects of a future higher-intensive rainfall climate with longer dry periods.Editor D. Koutsoyiannis;Associate editor D. Yang